Kinerja Dinas Penanaman Modal Dan PTSP Prov. Sumut Ditinjau Dari Peraturan Menteri Dalam Negeri (Permendagri) Nomor 25 Tahun 2021 - Riska Syahputri Nasution; Azhari Akmal Tarigan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Ministerial Regulations are regulations set by the minister depending on how the regulations will be used to carry out certain government affairs. DPMPTSP has the task of assisting regional heads in carrying out government affairs in the field of investment and one-stop integrated services, in accordance with Chapter III Article 4 of the Minister of Home Affairs Regulation (Permendagri) Number 25 of 2021. This research aims to examine the implementation of employee performance in the Provincial DPMPTSP North Sumatra is in accordance with Minister of Home Affairs Regulation Number 25 of 2021 which focuses on Chapter III Article 4. Data collection is carried out using the observation method. The findings of this study emphasize the importance of performance quality.